Identification and validation of a quantitative trait locus associated with wheat yellow mosaic virus pathotype I resistance in a Japanese wheat variety. Issue 4 (2nd June 2015) - Kojima, Hisayo; Nishio, Zenta; Kobayashi, Fuminori; Saito, Mika; Sasaya, Takahide; Kiribuchi‐Otobe, Chikako; Seki, Masako; Oda, Shunsuke; Nakamura, Toshiki; Ordon, F.
Abstract Yellow mosaic disease, caused by wheat yellow mosaic virus (WYMV), is one of the most serious diseases of winter wheat (Triticum aestivum L.) in Japan. The three pathotypes of WYMV are distributed in different geographical areas: pathotype I is found mainly in western and central Japan (Kanto), pathotype II in northern Japan (Tohoku and Hokkaido) and pathotype III on the southern island of Japan (Kyushu). A total of 246 doubled‐haploid (DH) lines, derived from a cross between 'Yumechikara' (resistant) and 'Kitahonami' (susceptible), were evaluated for 2 years for their resistance to WYMV pathotype I. A single major quantitative trait locus, Q.Ymym, mapping to chromosome 2D was associated with resistance to pathotype I in 'Yumechikara'. This is the first time a QTL responsible for pathotype I resistance has been identified. Fine mapping of Q.Ymym indicated that it was on a tight linkage block originating from 'Yumechikara', and the markers associated with this block will accelerate the development of varieties resistant to WYMV pathotype I.